2007
DOI: 10.1093/annonc/mdl425
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the value of FDG-PET and sentinel node biopsy to identify occult axillary metastases

Abstract: The high specificity of PET imaging indicates that patients who have a PET-positive axilla should have an ALND rather than an SNB for axillary staging. In contrast, FDG-PET showed poor sensitivity in the detection of axillary metastases, confirming the need for SNB in cases where PET is negative in the axilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
107
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 24 publications
2
107
0
3
Order By: Relevance
“…Several groups have demonstrated that, in most cases, FDG-PET or PET/CT has a low sensitivity (range 24-82 %) but a high specificity (range 80-100 %) and high positive predictive value (PPV) of more than 80 % [24][25][26][27][28][29][30][31][32][33]. In a review of 472 patients examined using FDG-PET/CT, the pooled sensitivity was relatively low (60 %) but the pooled specificity was very high (97 %) [34].…”
Section: Axillary Lymph Node Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have demonstrated that, in most cases, FDG-PET or PET/CT has a low sensitivity (range 24-82 %) but a high specificity (range 80-100 %) and high positive predictive value (PPV) of more than 80 % [24][25][26][27][28][29][30][31][32][33]. In a review of 472 patients examined using FDG-PET/CT, the pooled sensitivity was relatively low (60 %) but the pooled specificity was very high (97 %) [34].…”
Section: Axillary Lymph Node Stagingmentioning
confidence: 99%
“…In a review of 472 patients examined using FDG-PET/CT, the pooled sensitivity was relatively low (60 %) but the pooled specificity was very high (97 %) [34]. This high specificity and PPV of PET/CT imaging suggests that patients who have a PET-positive axilla should undergo ALND rather than SNB for axillary staging, reducing the need for unnecessary SLNB [25,34]. In contrast, PET/CT showed poor sensitivity for detection of axillary metastases, confirming the need for SLNB in cases where PET/CT findings are negative in the axilla.…”
Section: Axillary Lymph Node Stagingmentioning
confidence: 99%
“…tumours ≤2-3 cm and no palpable nodes that represent the majority of BC cases [3,4]. The low sensitivity of PET, compared to the sentinel node technique, in assessing axillary lymph node involvement is well-established [3] and the risk of distant metastases is low in early-stage disease.…”
mentioning
confidence: 99%
“…tumours ≤2-3 cm and no palpable nodes that represent the majority of BC cases [3,4]. The low sensitivity of PET, compared to the sentinel node technique, in assessing axillary lymph node involvement is well-established [3] and the risk of distant metastases is low in early-stage disease. The case is different in higher-risk BC patients in whom initial workup would usually comprise several imaging studies including ultrasonography of accessible lymph node basins, CT of the thorax and abdomen (or liver ultrasonography) and bone scan.…”
mentioning
confidence: 99%
“…18 F-FDG PET imaging has been demonstrated to play an important role in the management of patients with breast cancer, particularly in the assessment of tumour response to chemotherapy. Most published studies have assessed breast cancer response to neoadjuvant treatment [1][2][3][4][5][6][7][8] and interim chemotherapy evaluation (after the first and second cycle [1][2][3]), and have demonstrated a high correlation with pathological response or predicted outcome in patients with metastatic disease. In the present issue of the European Journal of Nuclear Medicine and Molecular Imaging, Mortazavi-Jehanno et al [9] report the results in 22 patients with recurrent or metastatic breast cancer at diagnosis who underwent serial FDG PET/CT before and after 8±2 weeks after the start of hormonal therapy.…”
mentioning
confidence: 99%